Political Strategy in Local Elections: Study of Bandung Municipality Mayor in the 2003 and 2008 Elections - Muslim Mufti (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to analyze the political strategies of candidates in the 2008 Bandung Mayoral Election. The research location is in Bandung Municipality, West Java Province. The research uses qualitative methods. The results of the study show that the candidates used political strategies to win the election. Those who acted as patrons won in the indirect election elected by the Regional House of Representatives (DPRD) of Bandung in 2003. Dada Rosada was a very influential figure in bureaucrat and government even though his party ranked third in the election. Politicians used political network strategy to convince the Partai Demokrasi Indonesia Perjuangan (PDIP) and the Partai Amanat Nasional (PAN) which were in first and second positions. The post-reform political strategy was different from the pre-reform, which was determined by the center. Hence, the role of politicians was decisive in the 2003 Bandung Mayoral Election which elected by the Regional House of Representatives. In the 2008 Bandung Mayoral Election, Dada Rosada used political network strategies to convince political elites and social network strategies to gain support and sympathy from the Bandung residents because it was directly elected by them.